Oestrogen enforces the integrity of blood vessels in the bone during pregnancy and menopause - Rodrigues, J; Wang, Y-F; Singh, A; Hendriks, M; Dharmalingam, G; Cohen-Solal, M; Kusumbe, A; Ramasamy, SK (Springer Nature, 2022)
The mammalian skeletal system shows sex differences in structure, functions, aging and disease incidences. The role of blood vessels in physiological, regenerative and pathological bone functions indicates the requisite to understanding their sex specificity. In this study, we found that estrogen regulates blood vessel physiology during pregnancy and menopause through estrogen receptor alpha (ERα) and G-protein-coupled estrogen receptor-1 (GPER1) but not ERβ-dependent signaling in mice. Estrogen regulates the lipid use of bone endothelial cells (BECs) and promotes lipolysis of adipocytes and fatty acid (FA) uptake from the microenvironment. Low estrogen conditions skew endothelial FA metabolism to accumulate lipid peroxides (LPOs), leading to vascular aging. High ferrous ion levels in female BECs intensify LPO accumulation and accelerate the aging process. Notably, inhibiting LPO generation using liproxstatin-1 in aged mice significantly improved bone heath. Thus, our findings demonstrate the effects of estrogen on BECs and suggest that LPO targeting could be an efficient strategy to manage blood and bone health in females.